The diversity and taxonomy of Aphonoidini (Orthoptera: Gryllidae; Podoscirtinae) from Singapore - Tan, Ming Kai (Zootaxa, 2022)
The diversity and taxonomy of Aphonoidini (Orthoptera, Gryllidae, Podoscirtinae) from Singapore are studied here. Prior to this study, three species were reported from Singapore: Aphonoides popovi Gorochov, 2007, Mistshenkoana nigrifrons Gorochov, 2007 [or M. angustifrons (Chopard 1930)] and Mistshenkoana gracilis (Chopard, 1925). Nevertheless, this is an underestimate of its diversity. Based on new specimens collected during recent surveys, eight species from four genera are now reported in Singapore. These include five new locality records for Singapore: Aphonoides ?cinereus (Haan, 1844); Dinomunda griseipennis (Chopard, 1969); Furcimunda furcilla Gorochov, 2007; Mistshenkoana bilineata (Chopard, 1954); Mistshenkoana hulu Gorochov, 2007. A key to the species of Aphonoidini is also presented.